Optimasi Komposisi Emulgator dalam Formulasi Krim Fraksi Etil Asetat Ekstrak Kulit Batang Nangka (Artocarpus heterophyllus Lamk) - Aldila Dina; Suwidjiyo Pramono; Nining Sugihartini (JURNAL ILMU KEFARMASIAN INDONESIA, 2017)
The jackfruit bark extract (A. heterophyllus) could inhibit the activity of tyrosinase enzyme. It was needed to be formulated as whitening cream. Cream formulation need emulsifi er to result physical properties and good stability. Aim of this study was to know the optimum composition of stearic acid and trietanolamine mixture as emulsifi ers in the jackfruit bark extract cream by using Factorial Design method. The fraction of the jackfruit bark extract was formulated in cream. The composition of stearic acid and trietanolamine were F1 (5:0,4), Fa (2,5:0,4), Fb (5:0,2) and Fab (2,5:0,2). The cream’s physical properties (spreadability, viscosity, viscosity shift) were evaluated. Data were analyzed by using Design Expert to obtain emulsifi er optimum composition. The result of study showed cream of jackfruit bark extract with variation of stearic acid and triethanolamine have a the viscosity value : 30628-37227 cps; spreadibility range from 5.20 to 6.80 cm and viscosity shift between 8.34% to 9.95%. The conclusion of this research is the formula that has optimum physical properties obtained by emulsifi er mixture composition of 3.22 gram stearic acid and 0.3 gram trietanolamine.